Best Orthogonal Trigonometric Approximations of Classes of Functions of Many Variables $L^{ψ}_{β, p}$ - Konsevich, N. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain order estimates for the best orthogonal trigonometric approximations of classes of functions of many variables L β, p ψ in the space L q, 1 < p < q < ∞, q > 2.